GAME HIJAIYAH BERBASIS WORDWALL UNTUK MENGENALKAN HURUF HIJAIYAH DI KB AGUNG KENCANA KECAMATAN SINGOSARI - Fauziyah, Ainul; Siti Muntomimah; Henni Anggraini (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
Teachers need to implement more innovative and interactive learning methods that align with the learning characteristics of early childhood, especially in introducing hijaiyah letters to young learners. This study aims to explore the use of a Wordwall-based hijaiyah game in introducing hijaiyah letters to early childhood students at KB Agung Kencana, Singosari District. The research employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, which includes the stages of planning, action, observation, and reflection, conducted in two cycles. The subjects of the study were 11 group A students at KB Agung Kencana. The results showed that the use of Wordwall media increased children’s participation, focus, and learning motivation. Learning outcomes improved progressively, from 55% in the pre-cycle phase to 92% at the end of the second cycle. This media not only made learning more engaging but also helped children recognize, point to, and pronounce hijaiyah letters more actively and enjoyably. Therefore, the use of Wordwall educational games has proven to be an effective medium for introducing hijaiyah letters to early childhood Keywords:  early childhood; hijaiyah letters; wordwall